Will Portugal turn into a second Greece? - Klaus Schrader; Claus-Friedrich Laaser (Kiel Institute for the World Economy (IfW), 2012)
Current economic developments in Portugal do not portend well. The Portuguese GDP is shrinking and the growth forecast for 2012 is gloomy - in the EU only the forecast for Greece is even worse (Figure 1). Moreover, Portugal is now having to pay double-digit interest rates on its bonds, its debt ratio exceeds 100 p.c. of GDP, its unemploy-ment rate is knocking on 15 p.c., and its current account deficit continues to remain high. All of these things not only indicate that Portugal is in a serious economic crisis. They also conjure up parallels to Greece's economic plunge. Thus, it is not surprising that many expect that Portugal will turn into a second Greece. But is this expectation really well founded? We think the answer to this question is no. A careful analysis of the crisis in Portugal shows that it is different from the crisis in Greece. Portugal has a better chance of avoiding economic collapse than Greece.
Keywords: 330; Wirtschaftskrise; Öffentliche Schulden; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Arbeitslosigkeit; Zins; Risikoprämie; Portugal